FACTORS AFFECTING TEACHER’S LEADERSHIP IN CURRENT SCENARIO: AN EMPIRICAL STUDY - Shankar, K.Tara; Yadav, Kanchan; Prakash, Chand (International Journal of Psychosocial Rehabilitation, 2020)
The role of effective cannot be overstated in an atmosphere where goal has been with each student to attain a high level. Leadership capacity is developed and supported at all rates within a productive educational environment. Advancement of educators is yet another aspect of governance. Teacher leadership is now in great supply from across the nation, in high schools and organizations. Teacher leading is the practice through which educators collaborate with the other faculty, staff, and community members to strengthen teaching strategies that enrich this educational environment and lead to higher teacher accomplishment. An effective way to help administrators and teachers incorporate new skills and strategies in their everyday work was its management approach. This same most significant factor in constructing a "great university" is effective leadership. Researchers in the present study wants to find out factors that enhance and influence the quality of leadership in school teachers, and the improvement of ethical leadership in high education.